COMMUNITY PHARMACISTS’ COUNSELLING SKILLS ON OVER-THE-COUNTER (OTC) MEDICATIONS - Elizabeth Yu Tan; Antonius Nugraha Widhi Pratama (UPT Penerbitan Universitas Jember)
Patient counseling is a responsibility of a pharmacist,more so, for a community pharmacist. It has alwaysbeen attached to the roles and responsibilities of apharmacist. Patient counselling is a growingdemand by patients who purchase medications inpharmacies. In Cebu City, patient counselling hasbeen observed to be rare to none by patients whichcan be attributed to many reasons. In a study, Issuesand Concerns on Utilization of the PharmacyWorkforce in the Philippines by Loquias and Robles(2012), the researchers found that pharmacists inthe community setting are hard to fill positions.Pharmacy owners hire even those who have noplans to stay. Due to the fast turnover ofpharmacists, training and development has becomemore costly for owners. This could meanunavailability of pharmacists in the drugstore atcertain times of the year to provide counselingservice. The community pharmacists are expected todo managerial tasks such as purchasing andinventory, sales monitoring, and even personnelsupervision which takes up most of the shift hours ofthe pharmacists. Patient counseling takes abackseat and is only provided when patients asks forit. In a study on Assessment of CommunityPharmacists Willingness and Barriers of MedicationTherapy Management (MTM) Focused on PainManagement and Mental Health by Keller, et al.(2014), community pharmacists strongly agreed thatthey will benefit from additional training on pain anddepression medication management. This is theexpressed concern community pharmacists in theUnited States of America who have a Doctor ofPharmacy (PharmD) degree and adequate training tomanage patients. The Pharmacy degree in thePhilippines is mostly Bachelor of Science inPharmacy and is a 4-year program versus the 6-yearprogram of PharmD. Ramanath et al. (2011) lookedinto the effect of a training module in improvingpatient counselling in the study. The researchersfound significant difference in the pre-post testscores of the pharmacists who participated in thetraining module. Participants also expressed theneed for more of such training in order to gainconfidence in patient counselling. The researchersare looking at the need to retool communitypharmacists so that they can be confident to counselpatients, especially those who are buying over-thecounter(OTC) medications. These are accessible topatients without prescription. In a prospective longtermmulti-centre study performed by Schmeidl, etal. (2014) on self-medication with over-the-counterand prescribed drugs causing adverse-drug-reactionsrelated to hospital admissions, it showed that whileself-medication does not really cause adverse drugreaction that leads to hospitalisation, the elderlypatients, and those receiving interacting prescribeddrugs may benefit with information from thecommunity pharmacists. The commonly seenadverse drug reactions are gastrointestinalcomplaints caused by NSAIDs.